IMPACT OF BANDITRY, INSURGENCIES, AND TERRORISM ON SCHOOL MANAGEMENT IN NIGERIA - Olowonefa , Jethro Abiodun (Multi-Disciplinary Research and Development Journals Int’l, 2025)
This paper explore the impact of banditry, insurgencies, and terrorism on school management in Nigeria. Depending on secondary data obtained from recognized online and print resources. The paper concluded that disruption of school operations and administration, threats to safety and security of school personnel and students, increased administrative and financial burden, staff shortages and low staff morale, decline in student enrollment and attendance, psychological and emotional challenges for school administrators, weakening of policy implementation and educational governance and destruction of school infrastructure and administrative records are direct impact of banditry, insurgencies and terrorism on school management in Nigeria. Based on The findings, the study recommends strengthening school security infrastructure, enhanced collaboration between schools and security agencies, increased funding and financial support for school management, capacity building and training for school administrators, psychosocial support for administrators, teachers, and students, community engagement and stakeholder participation, adoption of flexible and innovative administrative strategies, strengthening educational policies and legal frameworks, addressing root causes of insecurity and monitoring, evaluation, and research support.